2021
DOI: 10.1093/neuros/nyaa552
|View full text |Cite
|
Sign up to set email alerts
|

Postacute Cognitive Rehabilitation for Adult Brain Tumor Patients

Abstract: Intrinsic brain tumors often occur within functional neural networks, leading to neurological impairment and disability of varying degrees. Advances in our understanding of tumor-network integration, human cognition and language processing, and multiparametric imaging, combined with refined intraoperative tumor resection techniques, have enhanced surgical management of intrinsic brain tumors within eloquent areas. However, cognitive symptoms impacting health-related quality of life, particularly processing spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 107 publications
1
21
0
1
Order By: Relevance
“…It has been reported that neurological/neuropsychological deficits can recover after glioma surgery, and the postoperative follow-up period for recovery was 3-6 months [1,37]. A review of the usefulness of post-acute rehabilitation for brain tumors showed that the duration of intervention was 6 to 10 weeks [38]. Currently, there is no consensus on the possible recovery period after glioma surgery, but it is assumed that functional recovery reaches a plateau by 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that neurological/neuropsychological deficits can recover after glioma surgery, and the postoperative follow-up period for recovery was 3-6 months [1,37]. A review of the usefulness of post-acute rehabilitation for brain tumors showed that the duration of intervention was 6 to 10 weeks [38]. Currently, there is no consensus on the possible recovery period after glioma surgery, but it is assumed that functional recovery reaches a plateau by 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Given the emerging research for the use of cognitive rehabilitation for addressing cognitive and QoL concerns in LrGG (50)(51)(52)(53), this study underscores the value of including cognitive and QoL assessments as part of LrGG care, as well as highlighting the groundwork needed to refine cognitive treatments. More specifically, while still in its infancy for use in LrGG, cognitive rehabilitation models may want to consider how clinical factors such as age, T2 FLAIR volumes, tumor molecular characteristics, and treatment effects may jointly influence treatment response.…”
Section: Discussionmentioning
confidence: 80%
“…An impairment in at least one cognitive domain is seen in the majority of patients with intrinsic brain tumors such as low and high-grade gliomas [9]. Cognitive impairments experienced by cancer patients are associated with lower rates of return to work and poor quality of life therefore investigations focused on speech, cognition, and behavior have direct implications on clinical outcomes [8][9][10][11][12]. Patients who are considering enrollment in a non-therapeutic clinical research study, in which their doctor has a dual role as a treating physician and principal investigator, require special considerations.…”
Section: Neuro-oncology Contextmentioning
confidence: 99%
“…In the adult neuro-oncology patient population, over 70% of patients experience cognitive, language, or behavioral impairments, which negatively impacts outcomes [8][9][10][11][12]. Therefore, obtaining informed research consent may pose a challenge.…”
Section: Language and Cognitive Impairmentsmentioning
confidence: 99%
See 1 more Smart Citation